Comparison Between The Suspension and Capsule Preparation from Waste of Avocado Seeds As Antidiarrhea in Induced Mouse - Saputri, Muharni; Zebua, Nilsya Febrika; Asih, Fivi Nur; Putri, Ghera Fakhira (Universitas Muhammadiyah Yogyakarta, 2022)
Diarrhea is one type of disease with the most sufferers every year. Thus, it is considered an endemic disease in Indonesia and the potential disease of Extraordinary Events accompanied by mortality. One of the plants that can be used as a traditional medicine for diarrhea is the avocado seed, as it contains tannins, alkaloids, flavonoids, steroids and glycosides, which act as antidiarrheals. This study aims to determine the antidiarrheal effect of avocado seed extract suspension on mice induced by Oleum ricini and the optimum concentration of avocado seed extract suspension and capsules with an antidiarrheal effect in white male mice induced by Oleum ricini. The dosage forms chosen were suspension and capsules. This study used an experimental method with a test sample of the avocado seed. Avocado seed Simplicia was extracted by the percolation method, then an oral suspension and capsule formulation were made from the avocado seed methanol extract. It was evaluated and tested for its effectiveness with mice to cure diarrhea. Normal data were analyzed by One Way ANOVA and Post Hoc Tuckey Method. The results of this study showed that the administration of a suspension of avocado seed methanol extract at a dose of 800 mg/KgBB had the most optimum effect as an antidiarrheal against white male mice with a stool weight of 0.39 grams and a duration of diarrhea for 74 minutes. Furthermore, the administration of avocado seed extract capsules at a dose of 75 mg/KgBB had the most optimum effect as antidiarrheal against white male mice with Loperamide as a positive control. Therefore, it can be concluded that all suspension formulations and capsules of avocado seed methanol extract met the requirements for preparation evaluation. Suspension and avocado seed methanol extract capsules can cure diarrhea in white male mice.